1997
DOI: 10.1139/v97-167
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects on the reactivity of the silicon–carbon double bond. Arrhenius parameters for the reaction of 1,1 -diarylsilenes with alcohols and acetic acid

Abstract: Absolute rate constants for the reaction of a series of ring-substituted 1,1 -diphenylsilene derivatives with methanol, tert-butanol, and acetic acid in acetonitrile solution have been determined using nanosecond laser flash photolysis techniques. The three reactions exhibit small positive Hammett ρ-values at 23 °C, consistent with a mechanism involving initial, reversible nucleophilic attack at silicon to form a σ-bonded complex that collapses to product via rate-limiting proton transfer. Deuterium kinetic is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(102 citation statements)
references
References 0 publications
10
91
1
Order By: Relevance
“…18,20,21 The two silenes exhibit lifetimes of >5 µs in hexane and 1-4 µs in acetonitrile under these conditions and decay with mixed firstand second-order kinetics, with 1a being the longer-lived of the two. Much different behavior is observed in THF solution, where the lifetimes of the two silenes are longer, 1b is the longer-lived of the two, and their spectra are broadened and/or red-shifted as compared to hexane solution because of complexation with the ether solvent.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…18,20,21 The two silenes exhibit lifetimes of >5 µs in hexane and 1-4 µs in acetonitrile under these conditions and decay with mixed firstand second-order kinetics, with 1a being the longer-lived of the two. Much different behavior is observed in THF solution, where the lifetimes of the two silenes are longer, 1b is the longer-lived of the two, and their spectra are broadened and/or red-shifted as compared to hexane solution because of complexation with the ether solvent.…”
Section: Resultsmentioning
confidence: 95%
“…This behavior is also analogous to what has been observed previously for the addition of oxygen-centered nucleophiles to these two silenes. 15,18,21 In the case of oxygen-centered nucleophiles, we have recently shown that these trends are due, at least to some extent, to the effects of weak complexation of the free silene…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanosecond laser flash photolysis (NLFP) experiments employed a pulsed excimer laser filled with N 2 -He (337 nm, 4 mJ, 6 ns), Xe-HCl-He (308 nm, 55 mJ, 15 ns), or Kr-F 2 -N (248 nm, 100 mJ, 25 ns) for excitation, and a microcomputer-controlled detection system (19). Sample concentrations were such that the absorbance at the excitation wavelength (3-or 7-mm path length) was 0.2-0.9 and each sample was deoxygenated with argon or dry nitrogen until constant transient lifetimes were obtained.…”
Section: Resultsmentioning
confidence: 99%